THE EFFECT OF DIGITAL MARKETING AND BRAND IMAGE ON PATIENT VISIT DECISIONS AT VWXY HOSPITAL - Galin Mario Bimantara Purba; Endang Sulistyarini; Beby Karina Fawzeea Sembiring (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of digital marketing and brand image on patient visit decisions at a hospital. The background of this study is based on increasing competition among healthcare providers, which requires effective marketing strategies and strong brand positioning. This research uses a quantitative approach with multiple linear regression analysis. The results indicate that digital marketing has a strong and significant effect on patient visit decisions, with a correlation coefficient of 0.884 and regression coefficient of 0.544 (p < 0.001). Brand image also shows a strong influence, with a correlation coefficient of 0.875 and regression coefficient of 1.624 (p < 0.001). Simultaneously, both variables significantly affect visit decisions with an F value of 205.401 and significance of p < 0.001. The coefficient of determination (R²) is 0.820, meaning 82% of the variation in visit decisions is explained by digital marketing and brand image. These findings confirm that digital marketing and brand image are key determinants in influencing patient visit decisions.